Matrix card easy go / Noorzalyla Mokhtar … [et al.] - Mokhtar, Noorzalyla; Zakaria, Anis Mastura; Mohd. Som, Nazzatul Farhani; Zuhaidi, Nur Shafiqah; Md Sidek, Siti Nuraisyah; Ebrahim, Zarina Begum; Mustakim, Nurul Ain; Sauid, Muna Kameelah (Division of Research and Industry Linkages, 2017)
Matrix Card Easy Go is a device that is introduced to have functionalities of students' Identification card and storage capability. It can store student's documents and can be displayed at client’s PCs through cable connected using the USB port.